Tularemia vaccines - Putzova, Daniela; Senitkova, Iva; Stulik, Jiri (Folia microbiologica, 2016)
Francisella tularensis is the causative agent of the potentially lethal disease tularemia. Due to a low infectious dose and ease of airborne transmission, Francisella is classified as a category A biological agent. Despite the possible risk to public health, there is no safe and fully licensed vaccine. A potential vaccine candidate, an attenuated live vaccine strain, does not fulfil the criteria for general use. In this review, we will summarize existing and new candidates for live attenuated and subunit vaccines.
Keywords: bakteriální vakcíny; Tularemia; Francisella tularensis; Bacterial Vaccines; Animals; objevování léků; Drug Discovery; Humans; lidé; zvířata; tularemie